2023
DOI: 10.3389/fpsyg.2023.1128158
|View full text |Cite
|
Sign up to set email alerts
|

Risk of psychiatric readmission in the homeless population: A 10-year follow-up study

Abstract: Homelessness continues to be a major social and clinical problem. The homeless population has a higher burden of disease that includes psychiatric disorders. In addition, they have a lower use of ambulatory health services and a higher use of acute care. Few investigations analyze the use of services of this population group in the long term. We analyzed the risk of psychiatric readmission of homeless individuals through survival analysis. All admissions to a mental health hospitalization unit in the city of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Interestingly our results also indicated that while our matched controls were more likely to have no change to their hospitalizations, pGC cases were more likely to both have decreases or increases to their hospitalizations following pGC. Studies have investigated factors that lead to a reduction in psychiatric readmissions and patient characteristics, [35][36][37] which influence these psychiatric readmissions. Given that we controlled for several of these characteristics through our matching process, our results seem to suggest that pGC has an influence on decreasing hospitalizations for some individuals, while other individuals seem to be more inclined to utilize inpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly our results also indicated that while our matched controls were more likely to have no change to their hospitalizations, pGC cases were more likely to both have decreases or increases to their hospitalizations following pGC. Studies have investigated factors that lead to a reduction in psychiatric readmissions and patient characteristics, [35][36][37] which influence these psychiatric readmissions. Given that we controlled for several of these characteristics through our matching process, our results seem to suggest that pGC has an influence on decreasing hospitalizations for some individuals, while other individuals seem to be more inclined to utilize inpatient services.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for housing for a homeless patient during a psychiatric hospitalization is a challenging and difficult issue (21). A study in Canada revealed the need for adapted independent living options for psychiatric patients, but also more nursing homes and the increased specialization of existing residential resources (21). Homeless patients need shelter, and it is the duty of every facility to at least try to help find it when the patient is in admission.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we must dare to question how much capacity of psychiatric beds in hospitals may be occupied by patients who are ready for discharge but do not have housing. This situation, indeed, contributes to longer waiting lists and hinders the patient flow from admission to discharge (21). Another study revealed that all homeless patients with prolonged stay in an acute hospital were relocated to a long-term care institution because the complexity of these patients' needs increased the difficulty in finding appropriate resources in a timely manner (22).…”
Section: Discussionmentioning
confidence: 99%